PEMANFAATAN BUNGKIL INTI SAWIT SEBAGAI MEDIA PERTUMBUHAN CACING SUTRA (Tubifex sp.) - Putri, Berta; Hudaidah, Siti; Kesuma, Widi Indra (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2018)
The purpose of this research was to observe the effect of fermented palm kernel cake as a growth media for Tubifex sp. This research was conducted at the Aquaculture Laboratory, University of Lampung for 50 days. Completely Randomized Design (CDR) with 5 treatments and 3 replicates design is used for this experiment. The treatments are 100% field mud, 25% palm kernel cake :75% field mud, 50% palm kernel cake : 50% field mud, 75% palm kernel cake : 25% field mud, and 100% palm kernel cake. The data were analyzed with analysis of variance (ANOVA) continued with Least Significant Difference (LSD) test. The main parameters measured were Tubifex sp population and biomass as well as water quality parameters: pH, temperature, dissolved oxygen, and ammonia. The results showed that fermented palm kernel cake significantly (p<0,05) increase silk worm biomass and population. The best result of this research was found in 50% fermented palm kernel cake and 50% field mud media producing 111.008 ind/m2 and 750,72 gr/m2 of Tubifex sp. Water quality during Tubifex sp were measured at 0,26-0,91 mg/l ammonia, pH 6,14-7,11, temperature 25-28°C, and dissolved oxygen 2,9-3,9 mg/l.